ORAL PHYSIOLOGY AND TEXTURE PERCEPTION OF SEMISOLIDS - ENGELEN, LINA; VAN DER BILT, ANDRIES (Journal of texture studies, 2008)
In the oral cavity, the food is subjected to several mechanical and chemical processes. It is fractured by the teeth, diluted and broken down by saliva, heated or cooled by the ambient temperature of the mouth, formed into a bolus and finally swallowed. Numerous receptors in the oral cavity and nose respond to the initially ingested food and monitor the changes during processing. This leads to central perceptions of taste, odor, irritation and texture of the food. Most sensations associated with food texture occur only when the food is manipulated, deformed or moved across the oral receptors. In addition, people assessing the same stimulus differ in their ratings of that stimulus and their oral physiological parameters also exhibit inter-individual variations. This paper is based on the PhD thesis of one of the authors. It gives an overview of this study and includes related work of other authors. The aim of our research was to improve the understanding of oral texture perception, in particular to examine the role of oral physiological processes in oral texture perception of semisolids and to investigate whether individual differences in perception could be attributed to differences in oral physiology among subjects. The results of our study demonstrate that oral physiological parameters such as oral sensitivity, tongue movements, temperature and saliva composition are of importance for texture perception of semisolids. Many parameters of oral physiology correlate with various perceived texture attributes. This implies that intra-individual differences in texture perception could be attributed to variations in oral physiology. Oral physiology thus plays a role in texture perception of semisolids and should be taken into account in future texture research. By understanding the processes in the mouth while eating, a better understanding of the sensations and the perceptions of the food can be gained. Taking for each food the relevant physiological parameter into consideration when performing and designing rheological/instrumental measurements grants more natural conditions and better predictions of sensory perception. This could save time and money on time-consuming and expensive sensory panels in the earlier steps of product development and renovation. Knowing how physiological processes highlight specific flavor/texture sensations may be useful for product development or quality control where one typically wants to focus on certain sensations and ignores others. In addition, a future application could be to tailor products for personalized nutrition, individual choices or clinical nutrition based on physiological groups.